Energy and the national defense - Bucknell, Howard (Essays for the third century., 1981)
The Soviet invasion of Afghanistan and the war between Iran and Iraq underline the grim thesis of this book. Howard Bucknell argues that our dependence upon foreign oil poses an unequaled threat not only to our security as a nation but also to the fabric of our society. He issues a call for confronting this imminent crisis, for conservation and for the urgent development of new sources of energy.